Passivated graphene quantum dots for carbaryl determination in juices. Issue 8 (17th February 2021) - Soriano, M. Laura; Jiménez‐Sánchez, Andrés; Cárdenas, Soledad
Abstract: This paper reports a simple method for the preparation of suitable graphene quantum dots after surface passivation, to be used for the determination of carbaryl in juice samples. A comparison of synthetic conditions for the preparation of graphene quantum dots following the top‐down approach is described. In the one‐step route selected, evaluation of diverse reaction time for cutting and modulating the oxidizing sites in the broken pieces of the initial graphene layer is conducted with a mixture of concentrated acids. Exploring the passivation effect on the purified graphene quantum dots, we demonstrated the suitability of the selected graphene quantum dots for practical application in the detection of carbaryl using fluorometric detection. Higher sensitivity was achieved after 8 min of contact, in which graphene quantum dots promotes the degradation of carbaryl into naphthol, being the latter responsible for the analytical signal. The detection and quantification limits were 0.36 and 1.21 μg/L, respectively, being the response linear up to 26 μg/L with excellent precision (better than 3.2% at the limit of detection). The recovery of the analyte from commercial juice samples (91.4–96.7%) testifies to the applicability of the proposal for the analytical problem selected.